A Mn single atom catalyst with Mn–N2O2 sites integrated into carbon nanosheets for efficient electrocatalytic CO2 reduction. Issue 20 (26th April 2022) - Dong, Wenfei; Zhang, Nan; Li, Sanxiu; Min, Shixiong; Peng, Juan; Liu, Wanyi; Zhan, Dongping; Bai, Hongcun
Abstract : The presence of dual N, O- coordinated to the Mn single-atom catalyst with Mn–N2 O2 sites embedded in the 2D carbon nanosheets significantly improve catalytic activity for reduction of CO2 . Abstract : The electrocatalytic reduction of CO2 using electricity produced from renewable resources is a strategy for achieving CO2 emission reduction and sustainable energy development. Further, the reaction has a large number of industrial practical applications, since CO2 can be converted to fuels via downstream chemical processing of the CO product. Herein, we successfully synthesized a low Mn-content single-atom catalyst (SAC) with Mn–N2 O2 sites, covalently integrated into carbon nanosheets (Mn–NO/CNs) using a one-pot synthesis method. The Mn–NO/CN catalyst displays efficient electrocatalytic performance for the CO2 reduction reaction (CO2 RR). Using an H-type electrolytic cell, the maximum CO Faraday efficiency (FE) at −0.460 V (V vs. RHE) reaches 96.0% in 0.5 M KHCO3 electrolyte. In the flow cell measurements, Mn–NO/CNs exhibits a current density of 28 mA cm −2 at a very low potential of −0.425 V (V vs. RHE) for the CO2 RR with 1.0 M KOH as the mobile phase. The FECO remains above 80% even after 70 h, demonstrating the excellent durability of the catalyst even at a very low potential. The X-ray absorption spectra (XAS) and DFT calculations show that the Mn–N2 O2 site is the active catalytic center, which facilitates the adsorption of CO2 and significantly lowers the free energy barrier leading to the formation of the critical intermediate *COOH. The presence of dual N and O coordinated to the single atom metal sites embedded in the 2D carbon nanosheet significantly improves catalytic activity for the reduction of CO2 . Therefore, the catalytic performance of the single atom metal catalyst can be enhanced by adjusting the coordination environment.